Interfering with therapeutic tranquility: Debates surrounding biosolid waste processing in rural Ontario. (September 2016) - Mason-Renton, Sarah; Luginaah, Isaac
Abstract: Uncertainty surrounding potential health effects of techno-industrial facilities continues to result in heightened debate about what are the best and safest options for future generations in rural places regarded by residents for their therapeutic tranquility. This research examines how a proposed biosolid processing facility in rural Ontario producing agricultural fertilizer from primarily urban sewage has in some residents elicited particularly strong concerns about potential health impacts, which are accompanied by perceptions that the tranquil and pastoral nature of their landscape is being altered. However, fueling community conflict between friends and relatives is the contested nature of the landscape's restorative qualities and the facility's disruption of this tranquil place. Highlights: We examined residents' responses to biosolid processing in their community. We explored the perceived level of disruption to the landscape's tranquility. Perceived health impacts were influential in felt landscape disruption and facility opposition. The therapeutic nature of the landscape was contested within the community.